Calculation of the surface tension of liquid Ga-based alloys. Issue 13 (3rd May 2018) - Dogan, Ali; Arslan, Hüseyin
Abstract: As known, Eyring and his collaborators have applied the structure theory to the properties of binary liquid mixtures. In this work, the Eyring model has been extended to calculate the surface tension of liquid Ga–Bi, Ga–Sn and Ga–In binary alloys. It was found that the addition of Sn, In and Bi into Ga leads to significant decrease in the surface tension of the three Ga-based alloy systems, especially for that of Ga–Bi alloys. The calculated surface tension values of these alloys exhibit negative deviation from the corresponding ideal mixing isotherms. Moreover, a comparison between the calculated results and corresponding literature data indicates a good agreement.